Lipidomic analysis of bacterial plasmalogens - Řezanka, Tomáš; Křesinová, Zdena; Kolouchová, Irena; Sigler, Karel (Folia microbiologica, 2012)
Plasmalogens are a group of lipids with potentially important, and not yet fully known, functions in organisms from bacteria to protozoans, invertebrates, and mammals. They can protect cells against the damaging effects of reactive oxygen species, protect other phospholipids or lipoprotein particles against oxidative stress, and have been implicated as signaling molecules and modulators of membrane dynamics. They have been found in many anaerobic bacterial species, and their biosynthetic pathways differ in aerobic and anaerobic organisms. The use of advanced techniques permits the identification of not only plasmalogen classes but also their positional isomers and often also individual molecular species. This paper describes direct analyses of plasmalogens from natural sources, frequently very unusual, using electrospray ionization mass spectrometry in combination with high-performance liquid chromatography and/or shotgun lipidomics.
Keywords: molekulová hmotnost; Molecular Structure; molekulární struktura; Bacteria; Plasmalogens; plasmalogeny; Molecular Weight